2007
DOI: 10.1016/j.molcel.2007.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of HIF-1α Stability through S-Nitrosylation

Abstract: Hypoxia-inducible factor 1 (HIF-1) is a master transcriptional factor. Under normal oxygen tension, HIF-1 activity is usually suppressed due to the rapid, oxygen-dependent degradation of one of its two subunits, HIF-1alpha. Here we report that normoxic HIF-1 activity can be upregulated through NO-mediated S-nitrosylation and stabilization of HIF-1alpha. In murine tumors, exposure to ionizing radiation stimulated the generation of NO in tumor-associated macrophages. As a result, the HIF-1alpha protein is S-nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
354
4
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 403 publications
(373 citation statements)
references
References 51 publications
8
354
4
7
Order By: Relevance
“…HIF1 has been referred to as the "master regulator of oxygen homeostasis" 7 , but it is regulated by many factors aside from hypoxia, including oncogenes, growth factors and free radicals [27][28][29] . Free radicals are chemical species that contain unpaired electrons; of particular importance here are oxygen-containing radicals, such as the superoxide anion (O 2 -).…”
Section: Regulation Of Hif1 By Free Radicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…HIF1 has been referred to as the "master regulator of oxygen homeostasis" 7 , but it is regulated by many factors aside from hypoxia, including oncogenes, growth factors and free radicals [27][28][29] . Free radicals are chemical species that contain unpaired electrons; of particular importance here are oxygen-containing radicals, such as the superoxide anion (O 2 -).…”
Section: Regulation Of Hif1 By Free Radicalsmentioning
confidence: 99%
“…Exposure to NO has been shown to nitrosylate thiols in the HIF1α protein leading to HIF1α stabilization under aerobic conditions 39 . Recently, the specific target has been identified to be a cysteine residue in the ODD of HIF1α, which blocks its binding to the VHl complex for subsequent degradation 27 . NO can promote binding of HIF1 to HREs in HIF1 target genes by binding to an adjacent HIF1 ancillary sequence (HAs) and hence acting as a transcriptional co-activator 40 .…”
Section: Free Radical Regulation Of Hif1 Under Aerobic Conditionsmentioning
confidence: 99%
“…Many proteins that are reported to be regulated by S-nitrosothiol formation in the cardiovascular system have also been shown, most often previously, to be regulated by disulfides, often at the same cysteine residue. For example, S-nitrosation and disulfide formation has been shown to induce the same functional change in hypoxia-inducible factor 1α-subunit [92,93], caspase-3 [60,94], Na + /K + ATPase [95,96] and actin [84,97]. A summary of proteins that form S-nitrosothiols as well as disulfides is provided in Table 1, some of which are discussed in more detail below.…”
Section: Is No-dependent Signal Transduction Mediated By Stable S-nitmentioning
confidence: 99%
“…Although studies have shown that BMDCs increasingly infiltrate into tumours after irradiation and facilitate relapse 35 , they do not incorporate into the vasculature. Thus, these BMDCs do not participate in vasculogenesis as defined by Begg and colleagues and in the literature in general 1,6 .…”
mentioning
confidence: 99%
“…Thus, these BMDCs do not participate in vasculogenesis as defined by Begg and colleagues and in the literature in general 1,6 . Indeed, the BMDCs that are recruited by irradiated tumours are generally of myeloid lineage — including ‘alternatively’ activated macrophages and tyrosine protein kinase receptor (TIE2)-expressing monocytes (TEMs) — that facilitate post-irradiation tumour revascularization through paracrine mechanisms 25 . Distorting the definition of vasculogenesis not only confuses the literature but also misrepresents the biology — in this case by implying that the cells are doing something that they are not.…”
mentioning
confidence: 99%